SOSIALISASI PENYAKIT LAYU PISANG DAN CARA MEMBUAT BIBIT DARI MATA TUNAS DI DESA LEMBONGAN, KECAMATAN NUSA PENIDA KABUPATEN KLUNGKUNG - N. W. Suniti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
Training to control banana wild disease and to make the healthy banana seed with Persada biopesticide andBiota-L botanical pesticide was held at Lembongam village District of Nusa Penida, Klungkung regency on 28Juli 2012. Their activities were aimed to improve the farmer knowledge of banana wild disease and made thebanana healthy seed and control the banana wild disease. The topics covered were symptom of banana disease,bioecology pathogen, pathogen distribution, control of banana wild disease and made the banana healthy seedwith Persada biopesticide and Biota-L botanical pesticide. The training was attended by 31 participants from localfarmer of Lembongan village. The methods used in activities were lecture, trainning to make banana healthyseed, application of Persada biopesticide and Biota-l botanical pesticide in field. All farmers were interested inthis program because there was the new knowledge for them and they hope this to be continued in the future,